Computational study of the competitive binding of valproic acid glucuronide and carbapenem antibiotics to acylpeptide hydrolase. Issue 4 (August 2017) - Ishikawa, Takeshi; Otaki, Hiroki; Mizuta, Satoshi; Kuriyama, Masami; Onomura, Osamu; Higuchi, Norihide; Nakashima, Mihoko N.; Nakashima, Mikiro; Ohyama, Kaname
Abstract: The efficacy of the antiepileptic drug VPA is decreased by co-administered carbapenems (CBPMs). The mechanism of CBPM selective inhibition of acylpeptide hydrolase (APEH) hydrolysis of VPA-glucuronide (VPA-G) to VPA is unclear due to the lack of APEH structural information. Here we performed homology modeling of the three-dimensional structure of APEH and subsequent docking simulations with a modeled structure to understand this mechanism. Docking simulations indicated that four groups of binding structures were involved in the binding of VPA-G, panipenem, and meropenem to APEH, but only one or two binding structures were involved in the binding of meropenem with an open β-lactam ring structure and other antibiotics involving ampicillin. One of the four VPA-G binding structures was close enough to the APEH catalytic triad to facilitate VPA-G hydrolysis. This binding structure was also the most stable binding structure for panipenem, suggesting potential inhibition of VPA-G hydrolysis by panipenem. Fragment molecular orbital calculations of interaction energies of amino acid residues of APEH with VPA-G, panipenem, and meropenem indicated that the binding structure for panipenem closest to the catalytic triad is stabilized upon APEH interaction. These data suggest that APEH binding characteristics with CBPMs may help explain the selective inhibition of APEH by CBPMs. Graphical abstract: Docking simulations indicated that a β-lactam ring and an adjacent heterocycle are needed in order for this compound to be close to the catalytic triad of acylpeptide hydrolase.